1994
DOI: 10.1042/bj3010459
|View full text |Cite
|
Sign up to set email alerts
|

A possible route for the release of fatty acid from fatty acid-binding protein

Abstract: A simulation of the release of fatty acid from intestinal fatty acid-binding protein was attempted, starting with the crystallographic model and using molecular-dynamic processes at different temperatures. The release of the ligand was observed only at high temperature, which perhaps makes the process unreliable in detail. Nevertheless, the overall behaviour of the protein, also confirmed by the simulation performed at room temperature, strongly supports the idea that the fatty acid leaves the protein through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
5
15
1
1
Order By: Relevance
“…25,26 MD simulations of holo I-FABP, conducted at unrealistically high temperatures in order to observe the release of the ligand, indicated that bound fatty acid probably leaves the binding cavity through this portal. 27 Since water mobility is significantly higher than the mobility of a fatty acid, pathways for the exchange of internal water molecules in principle provide valuable information about possible routes for the fatty acid entry/exit. Thus we analyzed trajectories of individual water molecules that underwent either an internal 3 bulk or bulk 3 internal transition, specifically for the segments between the two states.…”
Section: Simulationsmentioning
confidence: 99%
“…25,26 MD simulations of holo I-FABP, conducted at unrealistically high temperatures in order to observe the release of the ligand, indicated that bound fatty acid probably leaves the binding cavity through this portal. 27 Since water mobility is significantly higher than the mobility of a fatty acid, pathways for the exchange of internal water molecules in principle provide valuable information about possible routes for the fatty acid entry/exit. Thus we analyzed trajectories of individual water molecules that underwent either an internal 3 bulk or bulk 3 internal transition, specifically for the segments between the two states.…”
Section: Simulationsmentioning
confidence: 99%
“…An extremely high temperature (1500 K) was used in an early report on intestinal FABP [21] to promote and speed up the dissociation process. More recently, a non-physical steering force was employed, either with constant direction [22] or randomly oriented [23], to favor dissociation of fatty acids from intestinal and liver FABP, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The application of computational methods to FABPs has been limited. One study used high-temperature dynamics to suggest possible routes for ligand release (Zanotti et al, 1994). Another assessed the conformational energy of the ligand in the x-ray structure of human muscle FABP (M-FABP) (Young et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical work explicitly assumed that the ligand carboxylate group is charged (e.g., Young et al, 1994;Zanotti et al, 1994;Rich and Evans, 1996). This assumption is also implicit in arguments for the importance of electrostatic effects in specific binding by I-FABP and CRBP-II (Jakoby et al, 1993).…”
Section: Introductionmentioning
confidence: 99%